De l'enseignement mutuel à la pédagogie différenciée : la place de l'enseignement simultané - Sabine Kahn; Elsa Roland
The aim of this article is to question the concept of differentiated pedagogy and the relationships it maintains with the structural organization of the existing school system and the perverse effects that this organization generates. A historical detour will be necessary to historicize this particular mode of school organization, whose roots go back to the 14th century, in which differentiated teaching took place in France, in Belgium and in many countries in the world : simultaneous teaching. This historical detour will allow us to identify in what way the organization of schooling could have been different. At the turn of the 18th century it was "mutual learning" that seemed more promising - a method that had proved to be particularly efficient and emancipatory, carrying an integrated pedagogical differentiation and serving the learning of all. It had a set of characters which overall probably contributed to accelerate its loss. Consequently, we will question the possibility of a differentiated instruction in a simultaneous school organization that may have limited capacity of integrating it.